Mineral Trioxide Aggregate and Calcium Hydroxide Promotes In Vivo Intratubular Mineralization - Reyes-Carmona DDS, MSD, PhD, Jessie (2016)
Literature showed that the interaction of Mineral Trioxide Aggregate (MTA) with dentin in phosphate-buffered saline (PBS) promotes a biomineralization process that leads to the formation of an interfacial layer with mineralized structures at the cement-dentin interface. Thus, we investigated the in vivo biomineralization process promoted by MTA and Ca(OH)² with dentin. Human dentin tubes filled with ProRoot MTA, Ca(OH)²  or kept empty were implanted in subcutaneous tissues in the back of mice. After 12h, 1, 3, 7, 15, 30 and 60 days, the dentin tubes were processed for Scanning Electron Microscope (SEM) observations. SEM examination showed the presence of apatite-like clusters on collagen fibrils over the surface of tubes containing the biomaterials. This mineral deposition was more extensive and compact through time. At day 7, a compact layer of apatite was formed. The MTA/Ca(OH)² -dentin interface showed intratubular mineralization as early as 12h post-implantation. MTA and Ca(OH)²  in an in vivo environment promoted a biomineralization process with dentin, simultaneously to the acute inflammatory response. MTA triggered an earlier and denser interfacial layer.